PEMEROLEHAN BAHASA PERTAMA PADA ANAK USIA DINI (PEMEROLEHAN FONOLOGI PADA ANAK 2 TAHUN) - Khairun Nisyah; Yusak Hudiyono (Bajang Institute, 2023)
This study aims to describe language acquisition in 2-year-old children. The researcher wants to know the language acquisition process of a child from the aspect of phonology. The child who is the object of this study has a fairly good level of language acquisition. However, in terms of phonology, there are still many errors in pronunciation. The method used in this research is descriptive qualitative method, which explains about language acquisition in children in terms of phonology. The data collection techniques were listening, engaging and speaking. The object of this research is a girl named Nahla Nasution, in interacting the child has been able to pronounce various forms of words and simple sentences. The results show that children are able to pronounce vocal elements (a, i, u, e, o) while consonant elements are still found some errors in pronunciation. This acquisition is influenced by the environment and stimulus given by parents to children, stimulus given by parents, one of which is by always reading books before bed and communicating with children like adults without changing words or sentences to sound funny.